(untitled) - Snitow, Alan (San Francisco, 2007)
The filmmakers who made the documentary Thirst have put together an account of the push for the privatization of public water works and the pillaging of the countryside as producers of bottled water play fast and loose with the water tables. The authors spotlight eight communities that have fought back against Big Water, and though each case is unique, there are trends. Water privatization is an expensive proposition, and many water companies are forced to "quickly slash costs and raise prices to maximize cash flow and pay down the debt.
Keywords: Water resources development,Privatization; Social aspects,Social aspects